Efficacy of High-Power Laser Therapy versus Pulsed Electromagnetic Field Therapy in Knee Osteoarthritis: High-Power Laser Therapy and Pulsed Electromagnetic Field Therapy in Knee Osteoarthritis - Nematollahi, Mehdi; Asif, Muhammad; Rashad, Abdul; Malaika, .; Wamiq, Alishba; Sandeela, Khadijatul Ain (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2025)
Knee osteoarthritis (OA) is one of the common musculoskeletal conditions causing pain, disability, and low quality of life. Alternative methods to conventional treatment have been put forward, like high-power laser therapy (HPLT) and pulsed electromagnetic field (PEMF) therapy, but data obtained have proved unsatisfactory. Objectives: To compare and contrast the short-term outcomes of HPLT and PEMF therapy on the reduction of pain and functional improvement in patients with knee osteoarthritis. Methods: A quasi-experimental design was used which was carried out in Shiraz, Iran, among 40 patients with knee OA (20 in each group). Group A was accorded HPLT, and Group B was accorded PEMF therapy for all 10 sessions. Visual Analogue Scale (VAS) and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) were used in the pre-intervention and post-intervention measures to determine the intensity of pain and physical function, respectively. Data were compared through paired t-test and ANOVA with p<0.05 as a significant value. Results: VAS and WOMAC scores significantly (p<0.05) reduced in both groups after the treatment. Intergroup comparison also demonstrated a great difference in VAS reduction where HPLT was more effective in relieving pain, although there was no significant difference in the WOMAC scores of the two groups. Conclusions: HPLT and PEMF treatment are effective in decreasing pain and enhancing the function in knee OA. The therapies demonstrated that HPLT was better in pain relief, and functional improvements were the same.